Microstructure Characteristics and Thickness Loss - Chadwick, Matthew (Dryad Digital Repository, 2019)
Measured characteristics (mineralogy, crystal density, organic content and Mg/Ca ratio) for each studied microstructure. Thickness loss values for each microstructure after 100 days under the two pH treatments (ambient and reduced). Values given as mean ± 1sd.